Commissioning and performance of TITAN’s Multiple-Reflection Time-of-Flight Mass-Spectrometer and isobar separator - Reiter, Moritz Pascal; Andrés, S. Ayet San; Bergmann, J.; Dickel, T.; Dilling, J.; Jacobs, A.; Kwiatkowski, A. A.; Plaß, W. R.; Scheidenberger, C.; Short, D.; Will, C.; Babcock, C.; et al. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2021)
TRIUMF’s Ion Trap for Atomic and Nuclear science (TITAN) has specialized in fast Penning Trap mass spectrometry of very short-lived radioactive isotopes. The facility has been upgraded with a Multiple-Reflection Time-of-Flight Mass Spectrometer (MR-TOF-MS) to continue its quest towards more exotic nuclides, which are critical for our understanding of nuclear structure effects far from the valley of beta stability and for the nucleosynthesis of heavy elements in explosive astrophysical environments. In this publication, we discuss the implementation, operation and performance of TITAN’s MR-TOF-MS as a stand-alone high-precision mass spectrometer and as an isobar separator. By using the novel mass-selective re-trapping technique for the isobar separation, the MR-TOF-MS can consecutively perform separation and mass measurement of the same ion population, acting as its own isobar separator. The device boosts the dynamic range and reach of the TITAN facility by several orders of magnitude. The MR-TOF-MS reaches a high mass resolving power (m/Δm∼400000), high precision and mass accuracy (δm/m<10−7), is fast (common cycle time 20ms), shows high sensitivity and very large dynamic range (ion of interest to contaminant ratios of up to 1 to 106).